Learning from Students' Voices to Build an Inclusive School - Marta Sandoval Mena (Universidad Autónoma de Madrid, 2016)
This article mainly covers an extensive literature review on the subject of the voice of the students in an inclusive research which considers the views, perspectives and supports' students are an invaluable contribution to build a school for everyone. It analyzes two modalities of participation, consultation and the students as researchers for being both forms the most frequent in the literature. In addition, the students in risk participation will be analyzed. Finally, we discuss some obstacles that researchers could find when research on this way.